KEANEKARAGAMAN FITOPLANKTON DI DANAU KENANGA UNIVERSITAS INDONESIA, JAWA BARAT - Rizal Koen Asharo; Pinta Omas Pasaribu; Vina Rizkawati; Rizky Priambodo; Abdul Hakim; Nur Wahyu Fathulhuda; Winda Nurul Fajriah; Muthiah Rahmah Ilahi; Nurul Assyifa Wardana (LPPM Universitas Negeri Jakarta, 2023)
In addition to urban forest area at the University of Indonesia, Depok Campus, West Java, there are lakes that functions as water reservoir area. University of Indonesia is eager to create green and beautiful campus environment with one of its efforts is to care for the lake ecosystem in the campus. This study was conducted to analyze the diversity of phytoplankton in the lake. Sampling was carried out by determining 3 location points with 3 times repetitions conducted on different days. The water samples taken were then identified at the Biology Laboratory FMIPA UNJ. The mean values of water quality parameters obtained were pH 10, TDS 90 ppm, temperature 30°C, and water clarity 46 cm. The results showed that 14 genera and 20 species have been found, they are Chlorophyta, Chroococcus, Coelosphaerium, Crucigeniella, Euglena, Gloeocapsa, Merismopedia, Pediastrum (3 species), Peridinium, Scenedesmus (4 species), Tablelaria, Tetrastrum, Volvox, and Westella (2 species). The Diversity Index Shannon-Wiener during the observation was 2.9, which means that the condition of water at the University of Indonesia Lake was very good and not polluted. The availability of phytoplankton in the area was generally sufficient which can be utilized by other organisms as food source.